The efficacy and potential mechanism of the acupuncture treatment for type 2 diabetes mellitus: A systematic review and meta-analysis of data from animal models - Lin, Linsun; Li, Shu; Guo, Ziyi; Fang, Peigang; Feng, Yanchen; Qi, Congcong; Wang, Mingyang; Xiao, Lu; Chen, Min; Wang, Tao (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a prevalent metabolic disorder with limited treatment options. Manual acupuncture and electroacupuncture have been investigated in numerous animal studies for their potential to improve glycemic and lipid profiles, but no comprehensive synthesis exists. This review aims to evaluate the effects of manual acupuncture and electroacupuncture on blood glucose and lipid levels in animal models of T2DM, and to explore potential mechanisms.MethodsA systematic search was conducted in PubMed, Embase, Cochrane, Web of Science, and major Chinese databases from inception to December 2024. Only animal studies employing manual acupuncture or electroacupuncture for T2DM models were included. The methodological quality was assessed using a 10-item CAMARADES checklist. Meta-analyses were performed using STATA 17.0, and subgroup analyses explored the influence of modeling methods, intervention timing, and treatment duration.ResultsA total of 14 studies with 274 animals with T2DM were included. The overall quality of the included reports was rated as moderate or higher. Meta-analysis showed that acupuncture significantly reduced blood glucose [Standardized Mean Difference(SMD)= -3.15, 95% Confidence Interval(CI) (-4.18, -2.12), I-squared (I²)= 85.1%, (P< 0.05)], body weight [SMD = -3.36, 95%CI (-4.77, -1.95), I²= 84.2%,(P<0.05)], triglycerides [SMD=-2.50, 95% CI (-3.00, -2.01), I²= 0.0%, (P< 0.05)], total cholesterol [SMD = -2.60, 95% CI (-3.55,-1.65), I²= 74.9%, (P< 0.05)], and low-density lipoprotein [SMD = -3.36, 95%CI (-5.42,-1.95), I²= 86.2%] (P< 0.05)], and no statistically significant difference was observed in high-density lipoprotein [SMD = 0.61, 95% CI (-0.98, 2.19), I² = 92.1%, (P> 0.05)] compared to the control group. These results suggest that acupuncture can effectively improve blood glucose and lipid levels in animal models of T2DM.ConclusionWhile this study is limited by the number of included studies, the results indicate that acupuncture can effectively improve blood glucose and lipid levels in animal models of T2DM.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024520000.